Sustainable decision-making model for municipal solid-waste management: bifuzzy approach - Termudi, Zamali; Abdullah, Mohd Lazim; Md Tap, Abu Osman (Universiti Malaysia Terengganu, 2012)
A sustainable model is observed as an important tool towards achieving the integrated municipal solid-waste (MSW) management decision. This paper proposes a new sustainable decision-making model to cope with this issue. The fuzzy analytic hierarchy process based on linguistics hedges combined with the fuzzy ideal solution was employed using the so-called conflicting bifuzzy-set approach. To ensure the model is well-suited with the local context, the input data was obtained entirely from the local stakeholders after attaining the consensus agreement among them. A case study in the state of Selangor and Kuala Lumpur Federal Territory was employed to demonstrate the feasibility of the proposed method. The model accommodates the integrated factors and is able to incorporate with the multiple stakeholders' so that the sustainable MSW management decision can be achieved successfully. © Untversiti Malaysia Terengganu.